Pretties - Westerfeld, Scott (Westerfeld, Scott. Uglies., 2011)
Tally takes full advantage of her newly acquired status of New Pretty to fill her social calendar with parties. She and her boyfriend, Zane, become addicted to drugs that make their minds increasingly able to focus. As Tally begins to remember how she became a Pretty, she starts to question the social order she is living in.